Rubber Plantation Land Grabs and Agrarian Change: A Political Economy Analysis of Livelihood Pathways of Ethnic Minority Groups in Northwest Vietnam - Luu Van Duy; Le Thi Thu Huong; Hiroshi Isoda; Yuichiro Amekawa; Le Thi Thanh Loan; Do Kim Chung (Land)
This paper critically examines the consequences of land grabs for livelihoods and agrarian change, based on a case study of rubber plantations in ethnic minorities in the uplands in Northwest Vietnam. Building upon Scoones’ agrarian political economy of livelihood framework, an integrated conceptual framework of a ‘livelihood pathway’ is developed to analyze the impact of rubber plantation land grabs on livelihoods and the agrarian political economy. Drawing on qualitative analysis and survey data from 205 households across six villages inhabited by Thai, Hmong, and Kho Mu communities, this study finds that rubber plantation land grabs have led to differentiated livelihood strategies—ranging from subsistence farming and wage labor to commercial agriculture—shaped by each group’s socioeconomic status, political connections, and access to resources. Consequently, the land grabbing undertaken by a domestic state-owned enterprise has caused the emergence of a set of distinctive livelihood pathways within a complex web of intersections across class and ethnicity in the upland area. This study concludes by arguing that an integrated conceptual framework of a ‘livelihood pathway’ offers a useful tool for analyzing the long-term socio-political consequences of land grabbing in similar contexts across developing countries and beyond.